Paediatric immunoglobulin A deficiency revisited - Gałęcki, Viktor; Janas, Michał; Juzyk, Piotr; Oronowicz, Radosław; Soloch, Martyna; Starczewski, Wojciech; Weigt, Agata; Szczawińska-Popłonyk, Aleksandra (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Immunoglobulin A (IgA) is the most abundant antibody isotype on mucosal surfaces, with predominantly neutralising non-activating functions, and which plays multifaceted roles in the immune system. IgA protects the host from pathogen invasion in the gastrointestinal and respiratory tracts, enhances diversification of microbiota, and maintains the intestinal homeostasis, exerting its twofold proinflammatory and anti-inflammatory functions by different immune cells and receptors. Therefore, IgA deficiency in children encompasses a broad spectrum of clinical phenotypes including infectious, allergic, autoimmune, and inflammatory conditions. In this review we also provide new insight into the genetic background and immunopathology of IgA deficiency in children.